Сравнительный анализ методов прогнозирования риска банкротства в условиях неопределенности - Зайченко, Ю. П. (Видавництво Львівської політехніки, 2011)
In this report different methods of bankruptcy forecasting are considered: the classical method of Altman,matrix method based on fuzzy sets and fuzzy neural networks. The experimental investigations of these methods application to bankruptcy risk analysis of Ukrainian corporations were carried out and its efficiency comparison is presented.
Keywords: bankruptcy risk analysis; forecasting fuzzy sets approach; fuzzy neural networks